Emotional labor as a mediator between workplace ostracism and emotional exhaustion in nursing professionals - Gou, L.; Ma, S.; Wang, G.; Zeng, W.; Wen, X.; Zhang, Y. (Modern Clinical Nursing, 2020)
Objective: To explore teh mediation role of emotional labor in teh relationship between workplace ostracism and emotional exhaustion, aiming to provide pratical implications to manage workplace ostracism. Methods: Using time-lagged survey, a total of 379 valid responses were collected at two time points from nurses in a tertiary hospital in Chengdu, including data of demographics,workplace ostracism, emotional labor (surface acting and deep acting) and emotional exhaustion. Structural Equation Model (SEM) was employed to test teh relationships. Results: Teh means of key variables were:workplace ostracism (1.39±0.45), surface acting (1.73±0.75), deep acting (2.94±0.83), and emotional exhaustion (3.53±1.17). There was a significant positive relationship between workplace ostracism and surface acting (p<0.001), just as well as teh relationship wif deep acting(p<0.01). Surface acting leads to emotional exhaustionof nurses (p<0.01) and mediates teh positive relationship between workplace ostracism and emotional exhaustion. Deep acting was not sngificantly related to emotional exhaustion(p>0.05). SEM analysis demonstrated an acceptable and reasonable model fit. Conclusion: Teh surveyed nurses reported a medium and low level of perceived workplace ostracism and emotional labor, but a high level of emotional exhaustion; Workplace ostracism TEMPhas a positive TEMPeffect on nurses’ emotional exhaustion via surface acting. Hospital administration should take measure to prevent and intervene workplace ostracism, to provide organizational and supervisory supports to nurses, and particularly to enhance nurse’s emotional management skills and encourage use of deep acting strategy to mitigage teh detrimental TEMPeffects of workplace ostracism.